Out-of-Plane bending behavior of a novel double steel plate concrete Composite-New tubular roof structure - Liang Yue; Yue Yang; Yi-Ran Liang; Li-Yan Xu; Jie Xu; Chen Wang (Tunnelling and Underground Space Technology, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Hydrodynamic-driven microbial community assembly and coalescence shape nitrogen transformation in river confluence - Cizhang Hui; Hongwu Tang; Qihua Ran; Dongfang Liang; Yi Li; Saiyu Yuan (ENGINEERING Environment, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

A multiscale risk operation and decision making model for inter-basin water diversion project under climate variability - Juan Chen; Zhen-ran Zhang; Yi-fan Liang; Xiao-hui Fan; Jian-qing Xie; Zhen Li; Ping-an Zhong (Environmental Research, 2026)

Regulate Root Stystem Development by Promoting NO Synthesis Via the NR Pathway after Iron Deficiency in Pears - Wankun Liu; Min Li; Min Liu; Jiankun Song; Chenglin Liang; Yingjie Yang; Dingli Li; Ran Wang; Yi Lv; Jianlong Liu (Journal of Plant Growth Regulation, 2026)

Responses of carbon monoxide photoproduction in surface seawater to environmental changes under simulated solar radiation - Xuan Ji; Ming-Liang Zhao; Yi-Ran Jia; Cai-Jie Zhang; Qi-Mei Du; Jing Zhang; Gui-Peng Yang (Marine Chemistry, 2026)

Curcumin-mediated photodynamic action disturbs TOM70-depedent MIC60 import to damage mitonchondria against breast cancer - Xiang-Yi Zhao; Min Yan; Liang Zheng; Chang-Long Gou; Qi Huang; Liu-Gen Li; Xin-Ran Yu; Jing-Yu Lu; Cui Hu; Si-Han Zhang; Cunqing Kong; Fan Leng; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

Close-packed metal organic frameworks enabled high-energy solid-state lithium metal batteries - Yining Zhang; Hongsheng Shi; Yuyao Zhang; Xin Chen; Shuanghong Wang; Jinjiang Liang; Qiong Yuan; Tianyi Gao; Ran Wei; Haochen Zhang; Tao Li; Tianquan Lin; et al. (Chemical Engineering Journal, 2026)

Regulatory mechanisms of total phosphorus on N2O concentrations: A case study of Dongting lake - Jie Liang; Yi Li; Weixiang Li; Ziqian Zhu; Xiang Gao; Ran Du; Lan Lu; Jing He; Chaozhong Tan; Rong Wu; Jikai Liao (Water Research, 2025)

Rapid and sensitive on-site detection of peach (Prunus persica) species in fruit juices using a RAA-CRISPR/Cas12a approach - Lin Wang; Ran-Ran Xing; Xiao-Ke Liang; Yao-Xian Yu; Qiu-Ju Yi; Si-Yuan Lu; Ting-Ting Deng; Jiu-Kai Zhang; Xu Wang; Ying Chen (Food Control, 2025)

Superior degradation of endocrine disruptors over defective iron pyrites assisted by vacancy-induced disassociation of hydrogen peroxide - Han-Liang Fang; Yu-Hang Xu; Xiang-Min Jin; Hao-Ran Long; Wen-Ni Zhang; Han-Hui You; Zhou Zhong; Yi-Dong Hou; Hai-Lei Cao; Christopher Rensing; Jian Lü (Chemical Engineering Journal, 2025)

Identification, Characterization, and Expression Profiling of Oryza Sativa Betaine Aldehyde Dehydrogenase Genes Exposed to Realistic Environmental Contamination of Oxyfluorfen - Yi Zhuo Wang; Jun Jin Lu; Xu Zhen Shi; Ya Nan Qu; Li Qing Zeng; Xiao Liang Liu; Xi Ran Cheng; Yan Hui Wang; Zhao Jie Chen (Tropical Plant Biology, 2025)

Identification, characterization, and expression profiling of putrescine synthesis genes associated with bentazone metabolism in Oryza sativa - Li Qing Zeng; Nian Hua Teng; Ying Yu Zeng; Zhi Jiang He; Yi Zhuo Wang; Zhi Zhong Zhou; Xiao Liang Liu; Xi Ran Cheng; Zhao Jie Chen (Genetic Resources and Crop Evolution, 2025)

Identification, characterization, and expression profiling of rice MADS-box transcription factor genes associated with fluroxypyr-meptyl and oxyfluorfen metabolism - Zhi Zhong Zhou; Nian Hua Teng; Jia Lin Liang; Ying Yu Zeng; Yi Zhuo Wang; Li Qing Zeng; Xiao Liang Liu; Xi Ran Cheng; Zhao Jie Chen (Genetica, 2025)

A ratiometric fluorescent probe for sensitive detection of benzoyl peroxide and hypochlorite in food - Shun-Qiang Cui; Xin-Yi Liang; Zhi-Qiang Cai; Hou-Qun Yuan; Qiu-Yu Zhang; Yi-Fan Xia; A.K.I.M.A.N.A. Sandra; Ling-Yi Guo; Ran Wang; Shi-Yu Zhao; Yan-Xia Li; Guang-Ming Bao (Food Chemistry, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

In situ transglutaminase cross-linking mediated protein-stabilized high internal phase emulsion gels to emulate dorsal adipose tissue: The role of continuous phase networks - Liang Guo; Yu-hang Xue; Yi-ran Zhang; Wen-yan Chen; Yao-siyi Yuan; Shen-shen Tian; Yue-Cheng Meng; Jie Chen (Food Chemistry, 2025)

Fluorinated Amino-acid-doped microarray-based biochemical patches Deciphers in-situ spatiotemporal dynamics amidst intricate Bio-Interfaces - Ru Zhang; Ran Duan; Deqi Yang; Haofan Wu; Bingfang Wang; Zhiqiang Chang; Jing Chen; Jing Dai; Yingying Lv; Yi Liu; Menahem Y. Rotenberg; Dandan Liang; et al. (Chemical Engineering Journal, 2025)

Trichothecenes with cytotoxic activity and benzene derivatives with hypolipidemic activity from trichothecium sp - Liang Xing; Yi-Fan Guo; Ke-Ran Hao; Yi-Ting Wu; An-An Yang (Natural Product Research, 2025)

Schistosoma japonicum cystatin attenuated CLP-induced sepsis in mice though inducing tolerogenic dendritic cells and regulatory T cells - Yi-Xiang Wang; Yi-Dan Ma; Hui-Hui Li; Wen-Juan Duo; Qi-Wang Jin; Kai-Jun Zhou; Yan-Ran Gao; Jun-Nan He; Yu-Jie Xie; Liang Chu; Xiao-Di Yang (Comparative Immunology, Microbiology and Infectious Diseases, 2025)

Antimicrobial p -terphenyl derivatives from the deep-sea cold seep-derived fungus Aspergillus candidus - Yi-Yi Liu; Jing-Ya Shi; Qi-Ran Liang; Guang-Ying Chen; Hai-Xin Chen; Zhuang Han; Xu-Hua Nong (Natural Product Research, 2025)

A comprehensive omics resource and genetic tools for functional genomics research and genetic improvement of sorghum - Chengxuan Chen; Fengyong Ge; Huilong Du; Yuanchang Sun; Yi Sui; Sanyuan Tang; Zhengwei Shen; Xuefeng Li; Huili Zhang; Cuo Mei; Peng Xie; Chao Li; et al. (Molecular Plant, 2025)

Targeting ferroptosis for the treatment of female reproductive system disorders - Rui Ye; Yi-ming Mao; Yi-ran Fei; Yue Shang; Ting zhang; Zhe-zhong Zhang; Yong-lin Liu; Jun-yu Li; Shi-liang Chen; Yi-bo He (Journal of Molecular Medicine, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Assessment of wetland ecological restoration effect based on fuzzy analytic hierarchy process: a case study of Tianjin Qilihai Wetland - Ran Zhou; Yi Zhang; Shitao Peng; Yisheng Wang; Mingxin Dai; Ningning Hong; Hui Tong; Baocui Liang; Shaopeng Lu; Wu Hong (Environmental Monitoring and Assessment, 2025)

Gigantic gastropods from the Middle Triassic Qingyan biota of Guizhou - Xin Sun; Li Tian; Chuan-Yuan Liu; Xiao He; Dao-Liang Chu; Xue Miao; Shi-Yan Zhang; Yi-Ran Cao; Pei-Shan Li; Jin-Nan Tong; Hai-Jun Song (Palaeoworld, 2024)

Freshwater microconchids from the Tanzhuang Formation (Middle-Late Triassic) in North China - Hao Yang; Yue Su; Hui-Jun Chen; Yi-Ran Cao; Meng-Yang Zhang; Rui Li; Dao-Liang Chu (Palaeoworld, 2024)

B/N modified carbon nanofiber mesh covered with layered double hydroxide for large current overall water splitting - Ji Qi; Chunqi Zhu; Jianing Hu; Shuai Ran; Tauqeer Ahmad; Siraj Ullah; Lixu Chen; Yi Chen; Yuqing Xia; Xue Sun; Chuang Li; Xiao Chen; et al. (Fuel, 2024)

Porous carbon prepared by thermal dissolution of coal and biomass for high-performance supercapacitors - Yi Liu; Wei-Dong Cao; Xing Fan; Ran-Ran Hou; Xiang Bai; Xiao-Yun Zhang; Yan Li; Guo-Ming Zhao; Peng Liang (Fuel, 2024)

Curvularin derivatives from the marine mangrove derived fungus Penicillium sumatrense MA-325 - Yi-Ran Wang; Yu-Liang Dong; Xiao-Ming Li; Xiao-Shan Shi; Hong-Lei Li; Ling-Hong Meng; Rui Xu; Bin-Gui Wang (Phytochemistry, 2024)

Controls on apatite compositional variations in magmatic rocks: A case study of Mesozoic mafic–felsic intrusions from the eastern North China Craton - Xiang-Yu Yan; De-Bin Yang; Wen-Liang Xu; Yi-Kang Quan; An-Qi Wang; Le-Ran Hao (Journal of Asian Earth Sciences, 2024)

Recycled crustal components in the depleted mantle source: Evidence from Early Cretaceous mafic rocks in the southern margin of the North China Craton - An-Qi Wang; De-Bin Yang; Wen-Liang Xu; Hao-Tian Yang; Yi-Kang Quan; Xiang-Yu Yan; Le-Ran Hao; Feng Wang (Lithos, 2024)

Three new glycosides from the stems of Eurya chinensis R. Br - Hui-Jun Liang; Qian-Ran Li; Bai-Lin Li; Chen Ni; Wei-Jie Zhang; Yu-Wen Fan; Zhuo-Yi Ao; Juan-Juan Hu; Jie Yuan; Jie-Wei Wu (Natural Product Research, 2024)

π-π Stacking constructing efficient charge channels for perovskite photovoltaics - Chun-Hao Chen; Fan Hu; Kai-Li Wang; Jing Chen; Tian-Yu Teng; Yi-Ran Shi; Yu Xia; Zhen-Huang Su; Xing-Yu Gao; Ilhan Yavuz; Zhao-Kui Wang; Liang-Sheng Liao (Science Bulletin, 2024)

Abnormal activation of the Wnt3a/β-catenin signaling pathway promotes the expression of T-box transcription factor 3(TBX3) and the epithelial-mesenchymal transition pathway to mediate the occurrence of adenomyosis - Mengqi Li; Ting Li; Tingting Jin; Yi Chen; Lan Cheng; Qiheng Liang; Simiao Yan; Tingting Li; Qingzhen Ran; Wanqun Chen (Molecular Biology Reports, 2023)

Degradation of Levofloxacin by a green zero-valent iron-loaded carbon composite activating peroxydisulfate system: Reactivity, products and mechanism - Shi-Ting Huang; Yong-Qian Lei; Peng-Ran Guo; Wen-Xuan Zhang; Jing-Yi Liang; Xie Chen; Jing-Wei Xu; Zeng-Hui Diao (Chemosphere, 2023)

Identification of metasomatic components in lithospheric mantle under multiple tectonic regimes: Insights from Early Cretaceous mafic rocks in the northeastern North China Craton - Xiang-Yu Yan; De-Bin Yang; Wen-Liang Xu; Yi-Kang Quan; An-Qi Wang; Le-Ran Hao; Feng Wang (Lithos, 2023)

Interspecific rootstocks improve the low-temperature resistance of bitter gourd through sucrose and nitrogen metabolism regulation - Le Liang; Huashan Lian; Huanxiu Li; Yiping Dong; Wanjia Tang; Ran Zhang; Xuemei Peng; Xiaomei Li; Yi Tang (Acta Physiologiae Plantarum, 2023)

Microbial electrochemical technologies assisted nitrogen recovery from different wastewater sources: Performance, life cycle assessment, and challenges - Siyuan Zhai; Dexin Zhang; Wenzong Liu; Bo Wang; Bin Liang; Chengyan Liu; Ran Zeng; Yanan Hou; Hao-Yi Cheng; Aijie Wang (Resources, Conservation and Recycling, 2023)

Yellow Petal locus GaYP promotes flavonol biosynthesis and yellow coloration in petals of Asiatic cotton (Gossypium arboreum) - Yaohua Li; Lingfang Ran; Tong Mo; Nian Liu; Jianyan Zeng; Aimin Liang; Chuannan Wang; Qingwei Suo; Zhong Chen; Yi Wang; Nianjuan Fang; Shijia Xu; et al. (Theoretical and Applied Genetics, 2023)

Identification of SNPs and candidate genes associated with early growth in orange-spotted grouper (Epinephelus coioides) by a genome-wide association study - Chun Hui Ai; Zong Xian Zhu; Dan Dan Huang; Gan Yang; Tong De Liu; Ying Bai; Xue Ying Liang; Ying Ying Xiong; Yi Long Lin; Hao Ran Lin; Shui Sheng Li; Jun Hong Xia (Aquaculture, 2023)

Repaired surface structural imperfection of tin Wide-Bandgap perovskite films for photovoltaic application - Tian-Yu Teng; Fan Hu; Yan-Hui Lou; Jun-Jie Cao; Chun-Hao Chen; Yi-Ran Shi; Kai-Li Wang; Jing Chen; Zhao-Kui Wang; Liang-Sheng Liao (Chemical Engineering Journal, 2023)

Apatite geochemistry from mafic rocks in the northeastern North China Craton: New insights into petrogenesis - Xiang-Yu Yan; De-Bin Yang; Wen-Liang Xu; Yi-Kang Quan; An-Qi Wang; Le-Ran Hao; Hao-Tian Yang; Feng Wang (Lithos, 2023)

Intercropping affects the physiology and cadmium absorption of pakchoi, lettuce, and radish seedlings - Le Liang; Xiaomei Li; Huanxiu Li; Xuemei Peng; Ran Zhang; Wanjia Tang; Yiping Dong; Yi Tang (Environmental Science and Pollution Research, 2023)

Apportioning above- and below-ground effects of moss biocrusts on soil detachment by overland flow in a subtropical climate - Guan-hua Zhang; Liang Yi; Wen-feng Ding; Xu Lei; Yi-ran Wang; Bao-yang Sun; Jian-ming Li (Journal of Mountain Science, 2021)

Epitranscriptomic technologies and analyses - Xiaoyu Li; Qiao-Xia Liang; Jin-Ran Lin; Jinying Peng; Jian-Hua Yang; Chengqi Yi; Yang Yu; Qiangfeng Cliff Zhang; Ke-Ren Zhou (Science China Life Sciences, 2020)

Perfluoroalkyl Substances in Water from the Yangtze River and Its Tributaries at the Dividing Point Between the Middle and Lower Reaches - Ke-Yan Tan; Guo-Hui Lu; Xin Yuan; Yu Zheng; Peng-Wei Shao; Jing-Yi Cai; Yi-Ran Zhao; Xiao-Hua Zhu; Yong-Liang Yang (Bulletin of Environmental Contamination and Toxicology, 2018)

Association of ulcerative colitis with transcobalamin II gene polymorphisms and serum homocysteine, vitamin B12, and folate levels in Chinese patients - Shuzi Zheng; Wei Yang; Chaoqun Wu; Liang Sun; Daopo Lin; Xiuqing Lin; Lijia Jiang; Ran Ding; Yi Jiang (Immunogenetics, 2017)

Complete genome sequence and comparative genome analysis of a new special Yersinia enterocolitica - Guoxiang Shi; Mingming Su; Junrong Liang; Ran Duan; Wenpeng Gu; Yuchun Xiao; Zhewen Zhang; Haiyan Qiu; Zheng Zhang; Yi Li; Xiaohe Zhang; Yunchao Ling; et al. (Archives of Microbiology, 2016)

Determination of royal jelly freshness by ELISA with a highly specific anti-apalbumin 1, major royal jelly protein 1 antibody - Li-rong Shen; Yi-ran Wang; Liang Zhai; Wen-xiu Zhou; Liang-liang Tan; Mei-lu Li; Dan-dan Liu; Fa Xiao (Journal of Zhejiang University-SCIENCE B, 2015)

The Antitumor Effect of a New Docetaxel-Loaded Microbubble Combined with Low-Frequency Ultrasound In Vitro: Preparation and Parameter Analysis - Shu-Ting Ren; Yi-Ran Liao; Xiao-Ning Kang; Yi-Ping Li; Hui Zhang; Hong Ai; Qiang Sun; Jing Jing; Xing-Hua Zhao; Li-Fang Tan; Xin-Liang Shen; Bing Wang (Pharmaceutical Research, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

An easy-to-use site-directed mutagenesis method with a designed restriction site for convenient and reliable mutant screening - Bao-zhong Zhang; Xin Zhang; Xiao-ping An; Duo-liang Ran; Yu-sen Zhou; Jun Lu; Yi-gang Tong (Journal of Zhejiang University-SCIENCE B, 2009)